PENGARUH DINAMIKA ORGANISASI TERHADAP EFEKTIVITAS PENEGAKAN HUKUM - Ghina Ulayya Hidayat; Deslita Kayla Nasywa, Prilanitasari, Tugimin Supriyadi (Adisam Publisher, 2024)
Effective law enforcement can prevent law violations and ensure justice for all citizens. This also prevents discrimination and maintains the integrity and integrity of society. However, there are still many problems in law enforcement in Indonesia. Some of these problems include corruption, slow judicial processes, and a weak judicial system. Dynamics can be interpreted as the movement or strength of a group of people in a society, which can cause changes in the lifestyle of that society. Dynamics can improve the performance of a system or process by increasing interaction and interdependence between group members. Organizational complexity and dynamics are factors that need attention in efforts to increase employee motivation and organizational productivity.